Contemporary Japan history, politics and social change since the 1980s - Kingston, Jeff (History of the contemporary world, 2013)
The second edition of this comprehensive study of recent Japanese history now includes the author's expert assessment of the effects of the earthquake and tsunami, including the political and environmental consequences of the Fukushima reactor meltdown.